Driving Prosperity: Assessing Empowerment, MSME Performance and Welfare: Mendorong Kesejahteraan: Menilai Pemberdayaan, Kinerja dan Kesejahteraan UMKM - Hadi, Nasrul; Mimiasri; Fitri, Aida; Saputra, Aiyub (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2023)
Micro, small, and medium-sized companies (MSMEs) play a critical role in improving societal well-being. However, empowering programs are critical to the success of MSME practitioners. Despite considerable initiatives in Banda Aceh to empower MSMEs, the direct impact on practitioner welfare remains unknown. The purpose of this quantitative study is to investigate the impact of empowerment effectiveness and MSME performance on practitioner wellbeing in Banda Aceh. The study includes 9691 MSMEs, based on data from the MSME Office of Cooperatives and MSME Aceh, and using random sample methodologies. A Likert scale was used for measurement. The data show that, while empowerment has a moderate impact on MSME welfare, MSME performance has a strong and meaningful influence. Furthermore, empowerment effectiveness and MSME success, when combined, contribute significantly to the welfare of MSME practitioners in Banda Aceh, accounting for 31.014% of the variance. This study emphasizes the necessity of not only empowering MSMEs but also improving their performance in order to significantly boost practitioner welfare